2015
DOI: 10.1002/2014gb004969
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl sulfide in the Amazon rain forest

Abstract: Surface-to-atmosphere emissions of dimethyl sulfide (DMS) may impact global climate through the formation of gaseous sulfuric acid, which can yield secondary sulfate aerosols and contribute to new particle formation. While oceans are generally considered the dominant sources of DMS, a shortage of ecosystem observations prevents an accurate analysis of terrestrial DMS sources. Using mass spectrometry, we quantified ambient DMS mixing ratios within and above a primary rainforest ecosystem in the central Amazon B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 65 publications
(107 reference statements)
4
75
0
Order By: Relevance
“…Furthermore, Jardine et al (2015) recently showed that DMS mixing ratios within and above a primary Amazonian rainforest ecosystem can reach levels of up to 160 pptv, in canopy and above the surface, for periods of up to 8 h during the evening and into the night, with levels peaking at 80 pptv above canopy.…”
Section: Discussion and Atmospheric Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Jardine et al (2015) recently showed that DMS mixing ratios within and above a primary Amazonian rainforest ecosystem can reach levels of up to 160 pptv, in canopy and above the surface, for periods of up to 8 h during the evening and into the night, with levels peaking at 80 pptv above canopy.…”
Section: Discussion and Atmospheric Implicationsmentioning
confidence: 99%
“…In a remote marine environment isoprene concentrations are probably an order of magnitude lower than this, and consequently [ISOP-SCI] would be calculated to be on the order of 4 × 10 1 molecules cm −3 . However, some regions will be impacted by both high isoprene and DMS concentrations, for example tropical islands, such as Borneo, which can have high isoprene concentrations and are strongly influenced by marine air masses (MacKenzie et al, 2011), as well as significant terrestrial sources from vegetation and soils in the Amazon, especially into the evening and at night (Jardine et al, 2015), when ozonolysis chemistry is at its most effective relative to photochemical OH chemistry. High sulfate composition of organic aerosols collected from the Borneo rainforests likely arises from the chemical processing of oceanic emissions of DMS and SO 2 (Hamilton et al, 2013).…”
Section: Discussion and Atmospheric Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details about the ATTO site infrastructure, instrumentation and an overview of running measurements can be found elsewhere (Andreae et al, 2015). Figure 1 shows the ATTO site location and the place of the Nyamuragira volcano in the DRC located at 1.41° S, 29.2° E, 3058 m a.s.l.…”
Section: Ground-based Instrumentationmentioning
confidence: 99%
“…In the Amazon rain forest, biogenic sulfate aerosol is sustained by oceanic DMS emission, and to a lesser degree by hydrogen sulfide (H 2 S), methanethiol (MeSH), and DMS emissions from soils and vegetation Jardine et al, 2015;Martin et al, 2010). Occasional anthropogenic sulfur injections have been attributed to open biomass burning and fossil fuel combustion emissions, either from Brazil or, via LRT, from Africa (Andreae et al, 1990;Talbot et al, 1988).…”
mentioning
confidence: 99%